Generation of NKX2.5GFP Reporter Human iPSCs and Differentiation Into Functional Cardiac Fibroblasts - López-Muneta, Leyre; Linares, Javier; Casis, Oscar; Martínez-Ibáñez, Laura; González Miqueo, Arantxa; Bezunartea, Jaione; Sanchez de la Nava, Ana Maria; Gallego, Mónica; Fernández-Santos, María Eugenia; Rodriguez-Madoz, Juan Roberto; Aranguren, Xabier L.; Fernández-Avilés, Francisco; et al. (Frontiers in Cell and Developmental Biology, 2022)
Direct cardiac reprogramming has emerged as an interesting approach for the treatment and regeneration of damaged hearts through the direct conversion of fibroblasts into cardiomyocytes or cardiovascular progenitors. However, in studies with human cells, the lack of reporter fibroblasts has hindered the screening of factors and consequently, the development of robust direct cardiac reprogramming protocols. In this study, we have generated functional human NKX2.5GFP reporter cardiac fibroblasts. We first established a new NKX2.5GFP reporter human induced pluripotent stem cell (hiPSC) line using a CRISPR-Cas9-based knock-in approach in order to preserve function which could alter the biology of the cells. The reporter was found to faithfully track NKX2.5 expressing cells in differentiated NKX2.5GFP hiPSC and the potential of NKX2.5-GFP+ cells to give rise to the expected cardiac lineages, including functional ventricular- and atrial-like cardiomyocytes, was demonstrated. Then NKX2.5GFP cardiac fibroblasts were obtained through directed differentiation, and these showed typical fibroblast-like morphology, a specific marker expression profile and, more importantly, functionality similar to patient-derived cardiac fibroblasts. The advantage of using this approach is that it offers an unlimited supply of cellular models for research in cardiac reprogramming, and since NKX2.5 is expressed not only in cardiomyocytes but also in cardiovascular precursors, the detection of both induced cell types would be possible. These reporter lines will be useful tools for human direct cardiac reprogramming research and progress in this field.